Size and scale effects in composites: III. Woven-roving laminates - Sutherlanda, L. S.; Shenoib, R. A.; Lewisc, S. M.
This paper is concerned with scale and size effects in the strength characterisation of composite materials with particular reference to woven-roving laminates. Attention has been focused on the tensile and flexural strengths of glass/polyester laminates fabricated by hand lay-up techniques. Factorial experiments have been designed to allow investigation of the joint influence of different factors on strength. The work highlights the importance of fabrication factors and the distinguishing difference between scale effects and size effects.
Keywords: SCALE EFFECTS; FRP; COMPOSITES; DIMENSIONAL ANALYSIS; WEIBULL ANALYSIS; FACTORIAL EXPERIMENTS